On an Inverse Problem of Reconstructing a Heat Conduction Process from Nonlocal Data - Makhmud A. Sadybekov; Gulnar Dildabek; Marina B. Ivanova (Advances in Mathematical Physics)
We consider an inverse problem for a one-dimensional heat equation with involution and with periodic boundary conditions with respect to a space variable. This problem simulates the process of heat propagation in a thin closed wire wrapped around a weakly permeable insulation. The inverse problem consists in the restoration (simultaneously with the solution) of an unknown right-hand side of the equation, which depends only on the spatial variable. The conditions for redefinition are initial and final states. Existence and uniqueness results for the given problem are obtained via the method of separation of variables.